Shikimic acid protects against doxorubicin-induced cardiotoxicity in rats - Maha Abdullah Alwaili; Amal S. Abu-Almakarem; Karim Samy El-Said; Thamir M. Eid; Maysa A. Mobasher; Ashwaq Hassan Alsabban; Najla Ali Alburae; Abeer A. Banjabi; Mohamed Mostafa Soliman (Scientific Reports, 2025)
Abstract Doxorubicin (DOX) is used to treat a variety of malignancies; however, its cardiotoxicity limits its effectiveness. Shikimic acid (SA) showed several promising biomedical applications. This study investigated the protective effect of SA on DOX-induced cardiotoxicity in male rats. The ADMETlab 2.0 web server was used to predict the pharmacokinetic properties of SA. Molecular docking studies were conducted using AutoDock Vina. Fifty male rats were divided into 4 groups (n = 10); G1 was a negative control; G2 was injected with 4 mg/kg of DOX intraperitoneally (i.p.) once a week for a month; G3 was gavaged by 1/10 of SA LD50 (280 mg/kg) daily for a month, and G4 was injected with DOX as in G2 and with SA as in G3. After a month, hematological, biochemical, molecular, and histopathological investigations were assessed. The results showed that SA treatment led to significant amelioration of the DOX-induced cardiotoxicity in rats by restoring hematological, biochemical, inflammatory biomarkers, antioxidant gene expression, and cardiac histopathological alterations. Importantly, the impact of SA treatment against DOX-promoted cardiac deterioration is by targeting the Nrf-2/Keap-1/HO-1/NQO-1 signaling pathway, which in turn induces the antioxidant agents. These findings suggest that SA treatment could potentially mitigate cardiac toxicity during DOX-based chemotherapy.